Nitrous Oxide (N2O) Emission And Agronomic Character On Different Green Bean Varieties (Vigna radiata L.) In Upland - Eni Yulianingsih; Rina Kartikawati; Sri Wahyuni (Agric, 2019)
Cultivation activities on mug bean lands have the potential to cause N2O emissions. Efforts to reduce N2O emissions through the selection of low-emission mug bean varieties. The study was conducted at the Experimental Garden of the Agricultural Environment Research Institute, Jaken, Pati, Central Java, in July 2018 until October 2018. The experimental design used was a randomized block design with six replications and four mug bean varieties: (1), Gronong (2), Menthik (3), PB and (4), Vima 3. Parameters measured were flux and N2O emissions, plant height, number of leaves, number of branches, leaf greenery, weight of 100 seeds, yield of dry beans per tile, and yields. The results of the analysis showes that PB varieties produced N2O emission values for the lowest 1 (one) growing season of 0.17 kg ha-1season-1. Meanwhile, from the results of productivity, the Menthik variety has the highest average yield of dried seeds, which is 1.38 tons ha-1. PB varieties have a higher average weight of 100 seeds (6.28 grams 100 seeds-1). So, in mung bean varieties that produce low emissions, not necessarily have high productivity as well. Greenhouse gas mitigation strategies, especially to reduce N2O emissions can be done by selecting varieties, balanced by good soil treatment, and effective and efficient fertilization.